Preparation method and application of sulfur passivation-resistant energy-saving hydrogen production coupled bifunctional electrocatalyst

By growing MoSe2 and NiSex through hydrothermal reaction on a foam nickel conductive substrate, the MoSe2/NiSex/NF electrocatalyst is formed, and the problem of catalyst in the prior art is solved, and efficient anti-passivation and electrocatalytic activity are achieved.

CN119506951APending Publication Date: 2025-02-25CHANGZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411446138.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the prior art, sulfur ion oxidation reaction (SOR) catalysts are prone to inactivation during sulfur passivation, and the single-phase selenide has insufficient conductivity, limited active sites, and poor electrocatalytic performance.

Method used

Molybdenum selenide and nickel selenide are grown on the foamed nickel conductive substrate through hydrothermal reaction, forming a coupled energy-saving hydrogen-producing dual-function electrocatalyst MoSe2/NiSex/NF, which is anti-sulfur passivation. This method utilizes a porous network of foam nickel and a multi-dimensional electron transfer path to improve the conductivity of the material and prevent catalyst agglomeration.

Benefits of technology

The catalyst is efficient anti-sulfur passivation, which improves electrocatalytic activity, avoids the deposition of elemental sulfur and the passivation of catalysts, has faster charge transfer and smaller interface resistance, and significantly improves the response ability of SOR reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506951A_ABST
    Figure CN119506951A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a sulfur passivation-resistant coupled energy-saving hydrogen production difunctional electrocatalyst, and relates to the technical field of preparation of energy-saving hydrogen production electrocatalysts, and the preparation method comprises the following steps: pretreatment of foamed nickel, hydrothermal reduction preparation of a MoSe2 / NiSex / NF catalyst, and coupled application of SOR and HER. According to the preparation method, a porous network and a multi-dimensional electron transfer path which are mutually connected in foamed nickel are utilized, and a high-temperature and high-pressure hydrothermal reduction method is adopted to anchor and grow a mixed phase component on a conductive substrate foamed nickel framework, so that effective compounding of multi-phase components is realized, and mass transfer and charge transfer are enhanced; the conductivity and the electrocatalytic activity are further improved; the prepared MoSe2 / NiSex / NF not only has the sulfur phobic characteristic, but also has selectivity on S < 2-> conversion, so that a polysulfide product instead of elemental sulfur is generated in the electrooxidation process, and the electrocatalytic activity of the MoSe2 / NiSex / NF in the long-term SOR process is maintained, thereby preparing the difunctional electrocatalyst with good conductivity, high catalytic activity and sulfur passivation resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalysis, and specifically relates to a preparation method and application of a coupled energy-saving hydrogen production bifunctional electrocatalyst that is resistant to sulfur passivation. Background Art

[0002] Hydrogen sulfide (H2S) is a toxic sulfide in common industrial waste and emissions. It not only causes serious pollution to the ecology and water resources, but also poses irreversible harm to human health. Therefore, the effective recovery of sulfides is crucial to environmental protection. Traditional recovery methods such as the Claus method, microwave catalysis, photochemistry and thermal decomposition face challenges due to high energy costs. In contrast, the sulfide oxidation reaction (SOR), as an electrochemical recovery scheme, has the advantages of high efficiency, low cost and simple operation. It can be paired with the cathode hydrogen evolution reaction. The sulfur products produced at the anode can be widely used in the application of industrial raw materials for fertilizer and rubber manufacturing, further improving the economic benefits, environmental benefits and energy benefits of the process, achieving multiple goals at one stroke. With the increasing demand for carbon-neutral energy, exploring electrocatalysts with excellent electrocatalytic activity plays a key role in the purification of sulfur-containing waste gas and the development of energy-saving hydrogen production.

[0003] At present, in existing studies, common SOR catalyst materials include alloys, metal oxides, metal sulfides, etc. Among them, the strong interaction or synergy of various metal atoms in alloys (binary alloys, medium entropy alloys, high entropy alloys) can usually improve the electrocatalytic performance, but often involve the participation of precious metals such as Pt, Ru, Ir, etc., which is costly and not suitable for industrial production; the polar bonds formed between metal cations and oxygen anions in metal oxides (precious metal oxides, transition metal oxides) can provide sufficient polar active sites for anchoring sulfides, but are easily passivated and poisoned during the SOR process, causing catalyst deactivation; metal sulfides (transition metal sulfides, precious metal sulfides) usually show better conductivity and show a beneficial affinity for sulfide electrolytes, but their electron transfer ability must be further enhanced and improved to realize the industrial application of this technology.

[0004] Recently, transition metal selenides have been widely studied due to their low cost, abundant terrestrial resources, and tunable properties. The 3d orbital energy levels of selenium in selenides are closely aligned with their 3s and 3p orbitals, allowing them to fully bind to metal atoms, which is beneficial for promoting electron transfer and sulfur conversion processes. Although selenides are considered to be potential electrocatalysts in SOR, single-phase selenides have insufficient conductivity, limited active sites, and poor electrocatalytic performance. In addition, sulfur passivation caused by elemental sulfur generated on the electrode surface during the SOR process will lead to a decrease in catalytic activity. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a coupled energy-saving hydrogen production bifunctional electrocatalyst that is resistant to sulfur passivation.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a coupled energy-saving hydrogen production bifunctional electrocatalyst that is resistant to sulfur passivation, comprising:

[0009] The nickel foam NF was ultrasonically treated in dilute hydrochloric acid, then rinsed with deionized water and anhydrous ethanol, and dried to obtain a three-dimensional porous nickel foam.

[0010] Mixing a selenium source and a reducing agent to prepare a solution A;

[0011] Mixing molybdenum salt with deionized water to prepare solution B;

[0012] Quickly pour solution B into solution A, and continue stirring to mix evenly to obtain a mixed solution;

[0013] Add nickel foam to the mixed solution and transfer it to a high-pressure reactor. Under high temperature and high pressure conditions, molybdenum selenide and nickel selenide are anchored and grown on the surface of nickel foam through hydrothermal reaction to obtain the catalyst MoSe2 / NiSe x / NF.

[0014] As a preferred embodiment of the preparation method of the present invention, the reaction temperature of the hydrothermal reaction is 180-220° C. and the reaction time is 2-5 hours.

[0015] As a preferred embodiment of the preparation method of the present invention, the reducing agent is one or more of urea, hydrazine hydrate, ammonia water, and NaBH4.

[0016] As a preferred embodiment of the preparation method of the present invention, the molybdenum salt comprises (NH4)6Mo7O 24 ·4H2O, Na2MoO4·2H2O or more thereof.

[0017] As a preferred embodiment of the preparation method of the present invention, the selenium source is one or more of Se powder, Na2SeO3, and SeO2.

[0018] As a preferred embodiment of the preparation method of the present invention, the size of the nickel foam NF is 1.5×1.0 cm.

[0019] As a preferred embodiment of the preparation method of the present invention, the concentration of the dilute hydrochloric acid is 2-5 M, and the ultrasonic time is 20-40 min.

[0020] As a preferred embodiment of the preparation method of the present invention, the total volume of solution A is 1 to 2 mL, the total volume of solution B is 7 to 12 mL, and the molar ratio of Mo:Se is 1.5:1 to 3:1.

[0021] Another object of the present invention is to overcome the deficiencies in the prior art and provide a coupled energy-saving hydrogen production bifunctional electrocatalyst that is resistant to sulfur passivation. The electrocatalyst is a nano-microsphere structure with a diameter of 2 to 5 μm.

[0022] Another object of the present invention is to overcome the deficiencies in the prior art and provide an application of an electrocatalyst in sulfur ion oxidation reaction.

[0023] Beneficial effects of the present invention:

[0024] (1) The present invention ingeniously utilizes hydrothermal reaction to convert MoSe2 and NiSe x Anchored and grown on a nickel foam conductive substrate, the electrical conductivity of the material is effectively improved and catalyst agglomeration is prevented by leveraging the advantages of nickel foam's interconnected porous network and multidimensional electron transfer pathways.

[0025] (2) Mixed phase MoSe2 / NiSe prepared by the present invention x The heterogeneous structure of MoSe2 / NiSe2 / NiSe2 effectively optimizes the electronic structure of the metal surface and ensures that the binding between the active catalyst and the reaction intermediate is neither too strong nor too weak, resulting in faster charge transfer and smaller interface resistance, further promoting interfacial electronic interaction and stronger response to sulfur oxidation, thus making MoSe2 / NiSe2 / NiSe2 x / NF can effectively capture polysulfides, making the composite phase material have better electrocatalytic activity than single-phase selenide.

[0026] (3) Mixed phase MoSe2 / NiSe prepared by the present invention x / NF can selectively convert S 2- / HS - Converted into polysulfide into high-valent polysulfide instead of elemental sulfur, avoiding sulfur passivation caused by the deposition of elemental sulfur on the catalyst surface; In addition, MoSe2 / NiSe x / NF also has sulfur-repellent properties to prevent sulfur from adhering to the catalyst surface, thereby achieving the self-cleaning and anti-passivation effect of the electrocatalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0028] Figure 1 MoSe2 / NiSe in the embodiment of the present invention x / NF XRD pattern;

[0029] Figure 2 MoSe2 / NiSe in the embodiment of the present invention x / SEM photo of NF;

[0030] Figure 3 1 and 2 are LSV curves of the electrochemical SOR and HER of the materials prepared in the embodiments of the present invention, wherein (a) is the LSV curve of SOR and (b) is the LSV curve of HER.

[0031] Figure 4 Based on MoSe2 / NiSe x LSV curves of SOR||HER and OER||HER coupling systems of / NF electrode;

[0032] Figure 5 MoSe2 / NiSe in the embodiment of the present invention x / NF sulfur contact angle image;

[0033] Figure 6 This is a UV-visible spectrum of the anode electrolyte diluted one hundred times after electrolysis for 15 hours in an embodiment of the present invention. DETAILED DESCRIPTION

[0034] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0035] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0036] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0037] The nickel foam in the embodiment of the present invention was purchased from Hefei Kejing Material Technology Co., Ltd., with specifications of: length 1000mm*width 300mm*thickness 1.6mm, 3N surface density 350g / m 2 ; Other raw materials are common commercially available products.

[0038] The present invention uses an X-ray diffractometer and a scanning electron microscope to characterize and analyze the comparative material prepared in this embodiment.

[0039] Evaluation of SOR and HER performance of the three-electrode system in the embodiment of the present invention:

[0040] (1) Preparation of working electrode: For powder samples, first ultrasonically disperse 4 mg of the prepared electrode material in a mixed solution of 261 μl of isopropanol, 652 μl of water and 87 μl of Nafion, and take 10 μL to coat on a rotating disk working electrode as the working electrode; for composite nickel foam samples, they can be directly used as the working electrode.

[0041] (2) SOR electrochemical performance test: The test was carried out on a CHI 660E electrochemical workstation. In the traditional three-electrode system, the synthesized catalyst was directly used as the working electrode, the platinum electrode was used as the counter electrode, Ag / AgCl was used as the reference electrode, and the electrolyte was 1.00 M NaOH + 1.00 M Na2S;

[0042] In the range of -0.2 to -1.0 V (relative to Ag / AgCl), the -1 The linear sweep voltammetry (LSV) curve was tested at a scan rate of , and 90% impedance compensation was adopted to obtain the final LSV curve.

[0043] (3) HER electrochemical performance test: The test was carried out on a CHI 660E electrochemical workstation. In the traditional three-electrode system, the synthesized catalyst was directly used as the working electrode, the platinum electrode was used as the counter electrode, Ag / AgCl was used as the reference electrode, and the electrolyte was 1.00M NaOH. The HER electrochemical performance was measured at 5mV·s in the range of 1.0-1.6V (relative to Ag / AgCl). -1 The LSV curve was tested at a scan rate of , and 90% impedance compensation was taken to obtain the final LSV curve.

[0044] Performance evaluation of the two-electrode SOR\\HER and OER\\HER coupling system in the embodiment of the present invention:

[0045] (1) Assembly and testing of SOR\\HER: The test was carried out on a CHI 660E electrochemical workstation, with the prepared catalyst as the working electrode, the platinum electrode as the counter electrode, the catholyte as 1.00 M NaOH, and the anolyte as 1.00 M NaOH + 1.00 M Na2S;

[0046] In the range of 0 to 0.8 V (relative to Ag / AgCl), the -1 The linear sweep voltammetry (LSV) curve was tested at a scan rate of , and 90% impedance compensation was adopted to obtain the final LSV curve.

[0047] (2) Assembly and testing of OER\\HER: The test was carried out on a CHI 660E electrochemical workstation, with the prepared catalyst as the working electrode, the platinum electrode as the counter electrode, and 1.00 M NaOH as the cathode and anode electrolytes;

[0048] In the range of 1.2 to 2.0 V (relative to Ag / AgCl), the -1 The linear sweep voltammetry (LSV) curve was tested at a scan rate of , and 90% impedance compensation was adopted to obtain the final LSV curve.

[0049] Example 1

[0050] MoSe2 / NiSe was synthesized as follows: x / NF:

[0051] (1) Pretreatment of conductive substrate nickel foam:

[0052] First, the nickel foam was cut into a size of 1.5 × 1.0 cm;

[0053] Subsequently, the cut nickel foam was ultrasonically treated in 3M dilute hydrochloric acid for 30 minutes to remove the oxide layer on the surface;

[0054] Finally, the sample was rinsed several times with deionized water and anhydrous ethanol to completely remove the dilute hydrochloric acid. After rinsing, the sample was dried at 60°C for later use.

[0055] (2) MoSe2 / NiSe x Preparation of / NF:

[0056] First, 1 / 3 mmol of Se powder was dissolved and dispersed in 2 mL of hydrazine hydrate and stirred for 1 h to obtain a red solution A.

[0057] Dissolve 2 / 3mmol Na2MoO4·2H2O in 8mL deionized water and stir for 0.5h to obtain a colorless solution B.

[0058] Then, the B solution was quickly poured into the A solution and magnetically stirred for 1 h. Three pieces of pretreated nickel foam were added to the mixed solution and transferred to a high-pressure reactor. The reaction temperature was 200 °C and the reaction time was 3 h.

[0059] After the reaction was completed and cooled to room temperature, it was rinsed several times with deionized water and anhydrous ethanol, and then dried at 60°C to obtain MoSe2 / NiSe x / NF samples.

[0060] Depend on Figure 1 It can be seen that MoSe2 / NiSe x The XRD patterns of the Mg / NF matched those of the standard cards of MoSe2 and NiSex, respectively, confirming the successful synthesis of the composites.

[0061] Depend on Figure 2 (a) It can be seen that MoSe2 / NiSe x It presents a nano-microsphere structure composed of nanosheet clusters; at the same time, MoSe2 / NiSe x The nickel foam skeleton is uniformly grown, and the nickel foam skeleton is kept intact ( Figure 2 (b)), which is beneficial to the mechanical strength of the material; the three-dimensional porous skeleton structure is conducive to the diffusion of gases in the electrocatalytic reaction and the full contact between the electrolyte and the active sites, thereby effectively improving its electrocatalytic activity.

[0062] Figure 5 MoSe2 / NiSe obtained by melting sulfur at 120°C x / NF sulfur contact angle picture, MoSe2 / NiSe x / NF has a larger sulfur contact angle, which indicates that the catalyst has sulfur-repellent properties, thus preventing the catalyst from being passivated and poisoned during the long-term SOR process.

[0063] In a typical three-electrode, 1M NaOH+1M Na2S was used as the electrolyte, Ag / AgCl was used as the reference electrode, Pt wire was used as the counter electrode, and the synthesized MoSe2 / NiSex / NF was used as the working electrode. The ISTP test was performed on the electrochemical workstation Chenhua 660e, with an applied current of 0.1A and a duration of 54000s. After the test, a certain amount of electrolyte was diluted 100 times and a spectrophotometer (Shimadzu, UV3600) was used to measure the UV-visible spectrum to obtain Figure 6 .

[0064] Depend on Figure 6It can be seen that MoSe2 / NiSe x After long-term SOR with NF as catalyst, polysulfide products (S x 2- , 2≤x≤4), no elemental sulfur was found, indicating that MoSe2 / NiSe x / NF can selectively convert S 2- / HS - It is converted into high-valent polysulfide compounds instead of elemental sulfur, thus avoiding sulfur passivation caused by the deposition of elemental sulfur on the catalyst surface.

[0065] In summary, MoSe2 / NiSe x / NF has good conductivity, high catalytic activity and resistance to SOR passivation, and is a highly promising multiphase composite electrocatalyst for coupling SOR and energy-saving hydrogen production.

[0066] Example 2

[0067] MoSe2 / NiSe was synthesized as follows: x powder:

[0068] (1) Pretreatment of conductive substrate nickel foam:

[0069] First, the nickel foam was cut into a size of 1.5 × 1.0 cm;

[0070] Subsequently, the cut nickel foam was ultrasonically treated in 3M dilute hydrochloric acid for 30 minutes to remove the oxide layer on the surface;

[0071] Finally, the sample was rinsed several times with deionized water and anhydrous ethanol to completely remove the dilute hydrochloric acid. After rinsing, the sample was dried at 60°C for later use.

[0072] (2) MoSe2 / NiSe x Preparation of powder:

[0073] Dissolve 1 / 3mmol Se powder in 2mL hydrazine hydrate and stir for 1h to obtain red solution A.

[0074] Dissolve 2 / 3mmol Na2MoO4·2H2O in 8mL deionized water and stir for 0.5h to obtain a colorless solution B.

[0075] Then, the B solution was quickly poured into the A solution and magnetically stirred for 1 h. Three pieces of pretreated nickel foam were added to the mixed solution and transferred to a high-pressure reactor. The reaction temperature was 200 °C and the reaction time was 3 h.

[0076] After the reaction is completed and cooled to room temperature, it is rinsed several times with deionized water and anhydrous ethanol, and then dried at 60°C;

[0077] The synthesized sample was placed in a 10 mL centrifuge tube, and 8 mL of ethanol was added and ultrasonicated several times to obtain a black powder. After washing, centrifugation, and drying, MoSe2 / NiSe x powder.

[0078] Example 3

[0079] NiSe was synthesized as follows: x / NF:

[0080] (1) Pretreatment of conductive substrate nickel foam:

[0081] First, the nickel foam was cut into a size of 1.5 × 1.0 cm;

[0082] Subsequently, the cut nickel foam was ultrasonically treated in 3M dilute hydrochloric acid for 30 minutes to remove the oxide layer on the surface;

[0083] Finally, the sample was rinsed several times with deionized water and anhydrous ethanol to completely remove the dilute hydrochloric acid. After rinsing, the sample was dried at 60°C for later use.

[0084] (2)NiSe x Preparation of / NF:

[0085] First, accurately measure 2 mL of hydrazine hydrate as solution A;

[0086] Dissolve 2 / 3mmol Na2MoO4·2H2O in 8mL deionized water and stir for 0.5h to obtain a colorless solution B.

[0087] Then, the B solution was quickly poured into the A solution and magnetically stirred for 1 h. Three pieces of pretreated nickel foam were added to the mixed solution, and the mixed solution was transferred to a high-pressure reactor. The reaction temperature was 200 °C and the reaction time was 3 h.

[0088] After the reaction was completed and cooled to room temperature, it was rinsed several times with deionized water and anhydrous ethanol, and then dried at 60°C to obtain NiSe x / NF samples.

[0089] Evaluation of electrocatalytic performance of three-electrode system:

[0090] The electrocatalytic SOR and HER performance of the examples were tested at 100 mA cm -2 The overpotential under current density was used as the evaluation standard for catalyst activity, and the results are shown in Table 1.

[0091] Table 1 Different catalysts at 100 mA cm -2 Comparison of overpotentials of SOR and HER at different current densities

[0092]

[0093] From Table 1, it can be seen that Example 1 MoSe2 / NiSe x The electrocatalytic activities of SOR and HER of / NF are significantly better than those of MoSe2 / NiSe x Powder and NiSe x / NF, indicating that the catalyst prepared by the present invention can increase the active sites on the catalyst surface by compounding with the conductive substrate nickel foam and designing a multi-phase composite selenide catalyst, thereby improving the catalyst's responsiveness to the sulfur oxidation reaction;

[0094] MoSe2 / NiSe x The LSV curves of electrochemical SOR and HER of / NF and Examples are shown in Figure 3 ,Depend on Figure 3 It can be seen that the mixed phase MoSe2 / NiSe x The electrocatalytic performance of the / NF electrode is significantly better than that of MoSe2 / NiSe x The performance of the powder shows that the conductive substrate nickel foam has an interconnected porous network that provides a multidimensional electron transfer path for the electrochemical reaction, effectively improving the electrocatalytic activity of the composite material. x / NF has a very poor electrocatalytic activity, indicating that the mixed phase MoSe2 / NiSe x / NF effectively optimizes the electronic structure of the selenide electrode, resulting in faster charge transfer and smaller interface resistance, which further promotes the interfacial electronic interaction, thus making MoSe2 / NiSe x / NF has better electrocatalytic activity.

[0095] That is, the catalyst prepared by the present invention can significantly reduce the energy input required for the reaction compared with conventional catalysts, which can not only achieve energy-saving hydrogen production, but also couple the purification of sulfur-containing exhaust gas.

[0096] Evaluation of electrocatalytic performance of two-electrode system:

[0097] Depend on Figure 4 It can be obtained that the SOR\\HER system is at 100mA·cm -2 The overpotential at the current density is only 0.613V, while that of the OER\\HER system is 2.035V, and the SOR\\HER system saves about 70% of the energy consumption. x The / NF-driven SOR\\HER system can not only purify sulfur-containing exhaust gas while producing hydrogen, but also greatly reduce energy consumption, further realizing the energy, economic and environmental benefits of the multifunctional catalyst.

[0098] Comparative Example 1

[0099] MoSe2 / NiSe with a Mo:Se ratio of 1.5:1 was synthesized as follows: x / NF-1.5:

[0100] (1) Pretreatment of conductive substrate nickel foam:

[0101] First, the nickel foam was cut into a size of 1.5 × 1.0 cm;

[0102] Subsequently, the cut nickel foam was ultrasonically treated in 3M dilute hydrochloric acid for 30 minutes to remove the oxide layer on the surface;

[0103] Finally, the sample was rinsed several times with deionized water and anhydrous ethanol to completely remove the dilute hydrochloric acid. After rinsing, the sample was dried at 60°C for later use.

[0104] (2) MoSe2 / NiSe x Preparation of / NF:

[0105] Dissolve 1 / 3mmol Se powder in 2mL hydrazine hydrate and stir for 1h to obtain red solution A.

[0106] Dissolve 1 / 2 mmol Na2MoO4·2H2O in 8 mL of deionized water and stir for 0.5 h to obtain a colorless solution B.

[0107] Then, the B solution was quickly poured into the A solution and magnetically stirred for 1 h. Three pieces of pretreated nickel foam were added to the mixed solution and transferred to a high-pressure reactor. The reaction temperature was 200 °C and the reaction time was 3 h.

[0108] After the reaction was completed and cooled to room temperature, it was rinsed several times with deionized water and anhydrous ethanol, and then dried at 60°C to obtain MoSe2 / NiSe x / NF-1.5 sample.

[0109] Comparative Example 2

[0110] MoSe2 / NiSe with a Mo:Se ratio of 3:1 was synthesized as follows: x / NF-3:

[0111] (1) Pretreatment of conductive substrate nickel foam:

[0112] First, the nickel foam was cut into a size of 1.5 × 1.0 cm;

[0113] Subsequently, the cut nickel foam was ultrasonically treated in 3M dilute hydrochloric acid for 30 minutes to remove the oxide layer on the surface;

[0114] Finally, the sample was rinsed several times with deionized water and anhydrous ethanol to completely remove the dilute hydrochloric acid. After rinsing, the sample was dried at 60°C for later use.

[0115] (2) MoSe2 / NiSe x Preparation of / NF:

[0116] Dissolve 1 / 3mmol Se powder in 2mL hydrazine hydrate and stir for 1h to obtain red solution A.

[0117] Dissolve 1 mmol of Na2MoO4·2H2O in 8 mL of deionized water and stir for 0.5 h to obtain a colorless solution B.

[0118] Then, the B solution was quickly poured into the A solution and magnetically stirred for 1 h. Three pieces of pretreated nickel foam were added to the mixed solution and transferred to a high-pressure reactor. The reaction temperature was 200 °C and the reaction time was 3 h.

[0119] After the reaction was completed and cooled to room temperature, it was rinsed several times with deionized water and anhydrous ethanol, and then dried at 60°C to obtain MoSe2 / NiSe x / NF-3 samples.

[0120] Evaluation of electrocatalytic performance of three-electrode system:

[0121] The electrocatalytic SOR and HER performance of the examples were tested at 100 mA cm -2 The overpotential under current density was used as the evaluation standard for catalyst activity, and the results are shown in Table 2.

[0122] Table 2

[0123]

[0124] As shown in Table 2, the HER and SOR performances of the samples with different Mo:Se in the comparative example are not good. This is because the ratio of the 2H phase with semiconductor characteristics and the 1T phase with metallic characteristics of MoSe2 in the sample is not appropriate, resulting in insufficient electrocatalytic active sites in the sample and poor electrocatalytic performance. It can be seen that reasonable regulation of the Mo:Se of the sample can optimize the ratio of 2H and 1T phases, making the sample rich in 1T phase, thereby effectively optimizing the electrocatalytic active center and reasonably optimizing the reaction energy barrier during the electrocatalytic reaction, so that the catalytic sample has good electrocatalytic activity.

[0125] In summary, in view of the long-standing problem of catalyst passivation caused by solid sulfur in the desulfurization process, the present invention effectively improves the anti-passivation self-cleaning ability of the catalyst from the following two aspects: 1) the catalyst is selectively generated into long-chain polysulfides rather than elemental sulfur during the sulfur oxidation reaction, thereby effectively avoiding sulfur passivation caused by the attachment of elemental sulfur to the catalyst surface; 2) the interfacial interaction between the catalyst surface and sulfur is rationally regulated, so that the prepared catalyst has sulfur-repellent properties, further avoiding the attachment and accumulation of elemental sulfur on the catalyst surface, thereby preparing a sulfur-oxygen electrocatalyst with good anti-passivation ability.

[0126] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A method for preparing a coupled energy-saving hydrogen production bifunctional electrocatalyst that is resistant to sulfur passivation, characterized in that: include, The nickel foam NF was ultrasonically treated in dilute hydrochloric acid, then rinsed with deionized water and anhydrous ethanol, and dried to obtain a three-dimensional porous nickel foam. Mixing a selenium source and a reducing agent to prepare a solution A; Mixing molybdenum salt with deionized water to prepare solution B; Quickly pour solution B into solution A, and continue stirring to mix evenly to obtain a mixed solution; Add nickel foam to the mixed solution and transfer it to a high-pressure reactor. Under high temperature and high pressure conditions, molybdenum selenide and nickel selenide are anchored and grown on the surface of nickel foam through hydrothermal reaction to obtain the catalyst MoSe2 / NiSe x / NF.

2. The preparation method according to claim 1, characterized in that: The reaction temperature of the hydrothermal reaction is 180-220° C., and the reaction time is 2-5 hours.

3. The preparation method according to claim 1 or 2, characterized in that: The reducing agent is one or more of urea, hydrazine hydrate, ammonia water, and NaBH4.

4. The preparation method according to claim 3, characterized in that: The molybdenum salt includes (NH4)6Mo7O 24 ·4H2O, Na2MoO4·2H2O or more thereof.

5. The preparation method according to claim 4, characterized in that: The selenium source is one or more of Se powder, Na2SeO3, and SeO2.

6. The preparation method according to claim 5, characterized in that: The size of the nickel foam NF is 1.5×1.0 cm.

7. The preparation method according to claim 6, characterized in that: The concentration of the dilute hydrochloric acid is 2-5 M, and the ultrasonic time is 20-40 min.

8. The preparation method according to any one of claims 1, 2, 4 to 7, characterized in that: The total volume of solution A is 1-2 mL, the total volume of solution B is 7-12 mL, and the molar ratio of Mo:Se is 1.5:1-3:

1.

9. The coupled energy-saving hydrogen production bifunctional electrocatalyst resistant to sulfur passivation prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The electrocatalyst is a nanometer microsphere structure with a diameter of 2 to 5 μm.

10. Use of the electrocatalyst according to claim 9 in a sulfide ion oxidation reaction.

Citation Information

Patent Citations

  • High-efficiency bimetallic nickel molybdenum selenide electro-catalytic material and preparation method thereof

    CN111495395A

  • Foamed nickel loaded sulfide electrocatalyst as well as preparation method and application thereof

    CN112962115A

  • Selenide composite material as well as preparation method and application thereof

    CN118166364A